Cycling outdoors facilitates external thoughts and endurance. (November 2016) - Slapsinskaite, Agne; García, Sergi; Razon, Selen; Balagué, Natàlia; Hristovski, Robert; Tenenbaum, Gershon
Abstract: Objectives: The aims of this study were twofold: (a) to compare the effects of indoor and outdoor environments on cycling endurance and thought dynamics, (b) to investigate a possible link between cycling endurance and the adherence to task-unrelated thoughts (TUT) in both environments. Design: An experimental, within-subject design with two-trial random assignment was used. Methods: Participants ( n = 13) cycled at constant power until volitional exhaustion while imposing TUT. They reported thought changes using self-selected key words that were subsequently classified based on task-relatedness (TUT, and task-related thoughts (TRT)) and direction (internal, external). Mean values of relative time spent in TUT and TRT categories were computed and compared for 5 equal time intervals. The association between cycling endurance and time spent at each thought-related category was analyzed. Results: Analyses revealed a decrease of TUT and an increase of TRT as a function of time (spent cycling) in both environments. Three qualitative thought phases emerged: an initially stable TUT phase was followed by a metastable phase characterized by shifts between TUT and TRT, and a final stable TRT phase appeared nearing exhaustion. Participants cycled longer outdoors than indoors M outdoors = 12.54 min, SEM = 2.17 s, M indoors = 11.35 min, SEM = 1.52 s ( Z = −2.27, p < 0.05, d (95% CI) = 0.56 (−0.80, 3.07)), with a dominance of external thought categories. Cycling endurance seemed to be facilitated by TUT-E outdoors and TRT-I in both types of environments. Conclusion: Outdoor environment resulted in improved cycling endurance and greater use of external thoughts (i.e., dissociative attentional strategy) relative to indoor environment. The effectiveness of thought categories seemed contingent upon their stability, which in turn depended on effort accumulation. Highlights: Cycling outdoors resulted in improved endurance compared to indoors. Cycling outdoors resulted in greater use of external thoughts. Three qualitative thought phases emerged in indoor and outdoor environments. Endurance was facilitated by TUT-E outdoors and by TRT-I in both environments. The effectiveness of thought categories seemed contingent upon their stability.